Counting the cost: the reserve price scheme for wool 1970‐2001. (3rd September 2019) - Abbott, Malcolm; Merrett, David
Abstract : This paper provides a policy commentary on the collapse in 1991 of the Australian Reserve Price Scheme for wool. A key cause of the collapse in the Scheme was a change in the RPS's governance arrangements, which led to increased political pressures to raise prices to unsustainable levels. In addition, in this paper an estimation has been made of the direct, upfront costs of the operation of the scheme, drawing on the financial accounts of the various agencies operating the RPS and subsequent wool stockpile. This was undertaken to determine the scale of the policy failure.